Religious Fanatic Subjects in the Postmodernism Era: the Meta-Theory of the Sociology of Religion Peter L. Berger - Agustinus Hadi Nugroho; Tito Briyan Diputra (BELIEF: Sociology of Religion Journal, 2023)
The tendency of every adherent of a religion or a sect of belief, it acknowledged or not, is fanaticism. It seems that there is not a single believer who will say that his religion is worse than any other religion. Every adherent of a religion will tend to defend their respective religions. Even if there is a difference, it only lies in the level of moderation; one is more open, while the other is more closed. In the book The Sacred Canopy: Elements of a Sociological Theory of Religion, Berger seeks to understand how religious belief is shaped at the individual and social levels. Furthermore, he wants to say, of course, latently, that religion is like a shell or canopy, which makes its adherents feel safe but at the same time, it is difficult to see other values that exist outside the spectrum of values of the truth of their religion. The nature of the religious belief system creates perspective restrictions and ideological tendencies. Berger's thoughts on the sociology of religion are still relevant today, especially in the context of a pluralistic Indonesian society in the context of caring for diversity. This research method is qualitative, with literacy study techniques that refer to Berger's works, as well as through literacy studies of other relevant writings. The results of this research are expected to enrich theoretical studies for sociology scholars, especially those interested in the sociology of religion.